Le rôle des ateliers de lampes dans la diffusion iconographique de la fuite d’Énée - Alexandra Dardenay (Mélanges de la Casa de Velázquez)
The study of a collection of baking detritus and other waste from terracotta lamps from a workshop in Merida prompts a discussion of the modes of circulation of the produce of a lampmaker’s shop in the capital of Roman Lusitania. The chosen group is homogeneous in character, not only in terms of the period of production (the Flavian era) but also in terms of the decoration on the lamp’s medallion, which depicts the flight of Aeneas – a motif popular in Roman times because of its political implications regarding the mythical origins of the gens Iulia. Analysis has shown that the product of the Merida workshop was in fact a recreation of a prototype made in Rome in the second half of the First Century AD. The article also examines the question of the limits of the area in which these lamps circulated and finally looks at some hypotheses regarding the relationship between lamps depicting the flight of Aeneas and popular expression of the imperial cult.